OPTIMIZATION OF HIGH STRENGTH CONCRETE - Patrisia, Yulin (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2015)
The production of high strength concrete using local materials, which are available in Surabaya and its surrounding area, that consider adequate slump so that the design is applicable in the project site, begin to be needed in the construction world. Through laboratory experiments, mix design using materials such as portland cement, silica fume, fly ash, coarse aggregate, fine aggregate, and also superplasticizer produces high strength concrete with cylinder compressive strength between 48 MPa – 93 MPa at 28 days age. By utilizing multiple regression analysis for data processing, a mathematical model for the designing composition of high strength concrete is proposed. The most factor that influences the compressive strength of concrete is the composition of silica fume, followed by composition of portland cement, finally the composition of water and fly ash.